Combining Optimal Controller and Luenberger Observer for an Active Roll Control System on Trucks to Avoid Rollover Phenomenon at High Speeds - Vu Van Tan; Pham Tat Thang; Do Trong Tu; Kieu Duc Thinh (Shock and Vibration)
The propensity for roll instability in automobiles, particularly trucks, often arises during high-speed maneuvers and emergency scenarios. The active roll control (ARC) system presents a promising solution for enhancing truck roll stability. This study delves into designing a controller for the ARC system adapted to high-speed truck operations. It entails formulating a cost function for the linear quadratic regulator (LQR) optimal controller, incorporating variables directly pertinent to truck roll stability: vehicle body’s roll angle, unsprung masses’ roll angle, and normalized load transfer at the two axles. To streamline sensor usage and prioritize cost-effectiveness, the Luenberger observer is integrated with the full-state feedback LQR controller. The investigation involves executing double lane change maneuvers, simulating overtaking and obstacle avoidance, at speeds of 70, 100, 130, and 160 km/h. The maximum absolute value of the normalized load transfer coefficient at the axles is assessed up to speeds of 200 km/h. Research findings underscore the efficacy of the ARC system in enhancing truck safety by reducing the normalized load transfer of all axles over 30% compared to the passive system, particularly during high-speed operations.